Dwelling performance and adaptive summer comfort in low-income Australian households. Issue 4 (19th May 2017) - Moore, Trivess; Ridley, Ian; Strengers, Yolande; Maller, Cecily; Horne, Ralph
ABSTRACT: Increasing reliance on air-conditioning to improve summertime comfort in dwellings results in higher energy bills, peak electricity demand and environmental issues. In pursuit of social equity, society needs to develop ways of improving cooling that are less reliant on air-conditioning. Designing homes to emphasize adaptive thermal comfort can reduce this reliance, particularly when combined with improved dwelling thermal performance. A multi-method evaluation of 10 low-income dwellings in the state of Victoria in Australia is presented, including low-energy and 'standard-performance' houses. The combination of performance monitoring and householder interviews reveals new insights for achieving summertime comfort. The low-energy houses without air-conditioning were both measured and perceived as more comfortable than the 'standard-performance' houses with air-conditioning. The low-energy households achieved improved personal thermal comfort through a combination of improved fabric performance augmented with adaptive comfort activities ( e.g., opening/closing windows). This outcome reduces reliance on air-conditioning, reduces living costs and energy consumption, and improves environmental outcomes. There is a need to integrate lessons from adaptive thermal comfort theory and strategies into minimum building performance requirements and standards, as well as wider design strategies. It is evident that adaptive comfort has a role to play in a transition to a low-carbon housing future.